Sports Marketing / A Strategic Perspective - Shank Matthew D (Pearson - Prentice Hall, 2005)
Business Perspective - Strategic Approach - Spotlight on Ethics - The Most Current Examples. Preface, Contingency Framework for Strategic Sports Marketing, Planning for Market Selection Decisions, Planning the Sports Marketing Mix, Implementing and Controlling the Strategic Sports Marketing Process, Index.